The Role of Parents in Learning During The Covid-19 Outbreak - Chusna Apriyanti (IJECA (International Journal of Education and Curriculum Application), 2021)
This research aims to know the parents' involvement, the sources used, parents' creativity, and the strategies used to widen the parents' concept of learning during the COVID-19 outbreak. This is descriptive quantitative research. The data were taken from 60 observers who observed the respondents' behavior in online learning. The respondents were the mothers of primary school students. The data were gathered from January 30, 2021, until February 15, 2021. The researcher collected the data by implementing these steps: posted the information for observers’ recruitment, made the instruments for the observers, the observers collected the data, the observers submitted the result of observation through Google Form. The result shows that most of the parents, 82% mothers involved in online learning, and 18% did not engage in the learning process. Most parents used textbooks and students' worksheets as learning sources (48%), followed by both (books and internet sources) 35%, internet sources 10%, and others 7%. In accompanying students' online learning, 85% of parents did not improve their learning media creativity, and 15% of parents were creative in handling online learning. The strategies used to widen the parents' creativity was using surroundings as learning media, including things, tools, activities, and settings.